Synthesis and biological evaluation of novel hybrid compounds between chalcone and piperazine as potential antitumor agents. Issue 10 (19th January 2016) - Mao, Zewei; Zheng, Xi; Qi, Yan; Zhang, Mengdi; Huang, Yao; Wan, Chunping; Rao, Gaoxiong
Abstract : A series of novel hybrid compounds between chalcone and piperazine have been synthesized, and their in vitro antitumor activity was evaluated against a panel of human tumor cell lines by MTT assay. Abstract : Chalcones play an important role in living organisms with a wide range of biological activities including potent antitumor activity. Previously, we reported that N -aryl piperazine compounds have excellent biological activity. To further explore the structure–activity relationships, a series of novel hybrid compounds between chalcone and piperazine have been synthesized, and their in vitro antitumor activity was evaluated against a panel of human tumor cell lines. The results demonstrated that compounds bearing acetophenone showed better anticancer activity than cisplatin and other hybrid compounds, and that substitution of the acetophenone with halogen atom, was vital for modulating cytotoxic activity. Among all synthetic derivatives, hybrid compound7c was found to be the most potent compound against A549, Hela and SGC7901 (IC50 = 5.24 μM, 0.19 μM and 0.41 μM, respectively), importantly, 7c exerted obvious inhibitory effect in vivo .